SPOKEN EXPRESSIONS OF VERBAL ORIGIN IN THE ASSEMBLY SPEECH (Philological Studies, 2019)
This paper is dedicated to the research of spoken expressions of the verbal origin in the speech of the National Assembly of the Republic of Serbia, founded on the base which comprises of 19 years of the Assembly sessions, 1997 to 2015. The issue which this dissertation is aiming to address is how the social and political elite, in the most significant institution deals with the segment of national tradition. This issue according to Fine's theory can also raise some more significant questions related to the whole society.
Keywords: spoken phrases of verbal origin, assembly speech, curses, oaths, blessings, proverbs, sayings, the National Assembly, members of parliament